ON EXEMPTION FROM INCOME TAXATION AT THE LEVEL OF THE "SUBSISTENCE MINIMUM (International Journal of Business, Law and Political Science, 2024)
The article deals with the introduction of non-taxable personal income, identifies the prospects for the effective organization of tax relations, presents relevant conclusions, scientific proposals and practical recommendations.